Localización de fallas en sistemas eléctricos de distribución basados en la matriz de impedancia de barra - Acuña Correa, Diego Patricio (2017)
This paper proposes a method of locating faults in electrical distribution systems based on bar impedance matrix, short circuit theory and intelligent metering using smart metering. The proposed method consists in locating these metering systems in different bars along the distribution system in order to obtain effective voltage values in the pre-fault and fault state, these quantities when operating with the bar impedance matrix obtain the failure current estimated by each phase in each bar. These currents are used to obtain the fault localization coefficient, with which a comparative analysis is carried out, determining the coefficient of smaller value indicated by the estimated fault bar. The method has been studied in the primary principle of the IEEE of 34 bars, for all types of fault, with different values of failure resistance, presenting satisfactory results.